Perlindungan Hukum terhadap Pekerja dengan Perjanjian Kerja Waktu di Indonesia - Agus Antara Putra; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Fakultas Hukum, Universitas Warmadewa, 2020)
In this day and age, norms often get blurred against the activities carried out by workers through a system of working agreements for a certain time. Workers get problems in the implementation of the regulation especially in fulfilling workers' rights which are not fulfilled by employers. This study aims to analyze the arrangements for a certain time work agreement in Indonesia, and to find out the legal protections for workers with a certain time working agreement in Indonesia. This study uses a normative legal research method through a statutory approach and a conceptual approach. The results show that the legal arrangements for a certain time work agreement in Indonesia have been regulated from the highest legal guidelines based on the 1945 Constitution to various Ministerial Decrees. Then, legal protection for workers with a work agreement for a certain time is carried out in a preventive and repressive manner. Supervision is also carried out to maintain the continuity of work agreements in accordance with statutory regulations.